Pathomorphological changes in lungs of deceased with obesity: review of literature and analysis of own observations. - Mazur, O. Yu.; Kuzyk, Yu. I. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Obesity is a disease that is characterized by excessive significant harmful effects on the functioning of almost all major systems of the human body. Pathological transformations of the lungs deserve particular attention, given the controversy of literary data relating to pathogenesis and morphological manifestations. The analysis of modern literature shows insufficient quantity and proof of the conducted researches. Objective. To find the morphological changes of the lungs and to establish the dependence of their genesis with the overall obesity by means of a retrospective analysis of protocols of autopsies and necropsy of deceased persons with obesity with the definition of pathomorphological changes of the pulmonary tissue. Methods. The authors analyzed 993 autopsy cases during the year of 2017 on the basis of the Lviv Regional Pathology Bureau. Obesity was detected in 67 death cases, of which 25 cases were randomly selected in order to objectify the detected changes in the lungs. The purposeful study of histological changes in lungs of 25 deceased with obesity has been carried out. Pulmonary tissue has been studied using standard histological techniques – hematoxylin-eosin staining. Results. Among the deceased patients there were 16 (64%) women and 9 (36%) men. The age of the patients ranged from 29 to 90 years. The average age of men was 60.88 ± 5.90; the average age of women was 67.31 ± 3.68. In 5 cases of the general investigation group no pulmonary pathology was detected. Among the 20 cases, the most commonly encountered pathology was pneumosclerosis (17 cases, 68% ). The second, most frequently detected pathology, was chronic bronchitis in the stage of exacerbation or remission (12 cases, 48%). Three cases (12%) were diagnosed with pulmonary thromboembolism: acute - 2 cases and one diagnosed case of recurrent pulmonary thromboembolism. Among other cases, there were pneumonias (3 cases), idiomatic pulmonary fibrosis and squamous cell carcinoma of the lungs. Conclusion. In investigation group of obese deceased, lung diseases were found in 80% of cases. Typical pathomorphological changes of the lungs in obese deceased were diffuse pneumosclerosis (whose correlation with sex and age is not detected) of varying degrees of generalization and chronic bronchitis.